Bagian Konservasi Gigi Fakultas Kedokteran Gigi Universitas Padjajaran Bandung, Indonesia - Mia Rachmawati; Moch. Richata Fadil; Endang Sukartini; Milly Armilia (DiscoverSys Inc., 2011)
One visit root canal treatment is one of the current treatment needs. Treatment includes cleansing, shaping, andobturation of the root canal sterilization is done in one visit. The purpose of one visit root canal treatment is toprevent the expansion of the pulp disease to the periapical tissues and restore normal periapical tissues. In thispaper, it is reported a woman, 28 year old, wanted to improve dental fillings of tooth 11 that have necrosis but haveno periapical lesions. Root canal treatment performed in one visit on tooth 11, which the result was satisfactory. Itcan be concluded that pulp necrosis without periapical lesions treated with one visit root canal treatment provedquite effective in seeing the results of clinical examination and radiographic post-treatment. However, it requiresknowledge, skills, adequate diagnosis and case selection, and employment of asepsis to the success of one visit rootcanal treatment.